PENGEMBANGAN APLIKASI GAMES EDUKATIF WORDWALL SEBAGAI MEDIA PEMBELAJARAN UNTUK MEMAHAMI MATERI PENDIDIKAN AGAMA ISLAM BAGI SISWA SD - Ani Nur Aeni; Dadan Djuanda; Maulana; Rini Nursaadah; Salsabila Baliani Putri Sopian (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the design and product development of PAI learning media for elementary school students in the form of Word Wall educative game application and to find out the effectiveness of applying Word Wall as measured from students' understanding of PAI learning subjects through Word Wall. The research was conducted to support teachers’competency in Technological Pedagogical Content Knowledge (TPACK). The research approach used is mixed-method with a 4-D development model design, defining, designing, developing, and disseminating. Data were obtained through questionnaire instruments, documentation, and interviews. The results indicate that 1) Word Wall product design is made based on the teacher need analysis on learning media in elementary school and based on curriculum analysis in the form of Basic Competency analysis and based on the second-grade elementary school students’ characteristics, 2) the products that are produced are Word Wall educative games, which consist of maze chase, airplane, balloon pop, and open the box, and 3) students' ability to understand PAI learning subject is very good through Word Wall games. Thus, the Word Wall application can be recommended and developed further on another Basic Competency through learning videos.